Binding of human syndecan to extracellular matrix proteins. - Klaus Elenius; Markku Salmivirta; Pirjo Inki; Markku Mali; Markku Jalkanen (1990)
We have isolated a cell surface proteoglycan from a human mammary cell line (HBL-100). This proteoglycan was found to be a human equivalent to mouse syndecan, because (i) it has identical biochemical properties with murine syndecan, including size, charge, buoyant density, and glycosaminoglycan composition, (ii) its core protein has identical size with murine syndecan as studied by sodium dodecyl sulfate-polyacrylamide gel electrophoresis, and (iii) the core protein is detected with anti-peptide antibody for the cytoplasmic domain of syndecan. HBL-100 cells also showed high expression of syndecan mRNAs, when probed with mouse syndecan cDNA. The ectodomain of the human syndecan revealed binding to type I collagen fibrils and fibronectin but not to laminin, duplicating the binding properties of murine syndecan. Very interestingly, syndecan did not bind to vitronectin, which is known to contain a heparin binding domain and is one of the major adhesive factors of serum for cultured cells. Syndecans are known to change their glycosaminoglycan composition yielding tissue-type specific polymorphic forms of syndecan (Sanderson, R., and Bernfield, M. (1988) Proc. Natl. Acad. Sci. U. S.A. 85, 9562-9566). The members of this family may thus represent a collection of structurally related matrix receptors that could differ in their interactions due to variation of the ectodomain glycosylation.